USING TPR (TOTAL PHYSICAL RESPONSE) METHOD FOR YOUNG LEARNERS IN LEARNING ENGLISH VOCABULARY - As’ad, Riska Dwi Putri; Noni, Nurdin; Samtidar, Samtidar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to gather empirical evidence on whether there is a significant difference in students' achievement in understanding English vocabulary when using the TPR method compared to those who do not. The researcher conducted this study in grades V (A and B) of SDN 5 Maros, located at Jl. Lanto Dg. Pasewang No. 12, Maros. In this study, the researcher used the quasi-experimental method by selecting two groups as research samples, namely the experimental and control classes. The researcher used purposive sampling as a sampling technique because it could provide the information needed in the study. The researcher chose class V A as the experimental class and class V B as the control class. In addition, these two classes were more accessible, so the researcher chose them as research subjects. The research subjects totaled 42 students. The authors conducted a pre-test in both classes before carrying out the treatment. In addition, the researchers used the TPR Method to teach English vocabulary in the experimental class. After the treatment, a post-test was conducted in both classes to determine the effectiveness of the TPR Method in teaching English vocabulary in the experimental class. From the study results, it was found that after receiving treatment with the TPR method, the experimental class experienced a significant improvement in English vocabulary acquisition. Although initially, they had lower pre-test scores than the control class (84.4% vs 88.3%), after the treatment, they recorded a considerable improvement in the post-test (88.8%). This shows that the TPR method is effective in helping learners understand and remember English vocabulary well.Keywords: TPR Method,;Young Learners; English Vocabulary